Chad : Requests for Disbursement under the Rapid Credit Facility, Extension of the Extended Credit Facility Arrangement, and Rephasing of Access-Press Release; Staff Report; and Statement by the Executive Director for Chad. (IMF Staff Country Reports; Country Report ;, 2020)
This paper presents Chad's Requests for Disbursement Under the Rapid Credit Facility, Extension of the Extended Credit Facility Arrangement, and Rephasing of Access. In response to the coronavirus disease 2019 outbreak, the authorities have taken strong measures to halt the community spread of the virus. They are also scaling up health-related spending and are considering a set of economic measures to support households and businesses. Given the sudden nature of the shocks and their widespread impact, the authorities will be temporarily relaxing the fiscal deficit to allow for the scaling up of health care spending and to accommodate the impact of the sharp drop in oil prices. In order to safeguard debt sustainability, they remain committed to the medium-term fiscal path and will implement the needed adjustment measures as soon as the current crisis abates.